Direct Democracy and Political Equality in the American States*. (28th July 2014) - Flavin, Patrick
<x xml:space="preserve">Abstract</x> Objectives This study investigates the relationship between direct democracy and the equality of opinion‐policy representation in the American states. Methods Using public opinion measures from the National Annenberg Election Surveys and data on state policy outputs, I generate an index of the equality of political representation (based on citizens' incomes) that is comparable across the states. I then evaluate the relationship between different measures of direct democracy and political equality. Results States with the ballot initiative process are no more politically equal than states without the process. However, among those that have the ballot initiative process, states where it is easier to place a measure on the ballot for popular vote and states where the ballot initiative is more frequently used tend to weigh citizens' opinions more equally in the policy‐making process. Conclusion These findings suggest that having and frequently using direct democracy leads to more egalitarian policy outcomes. More generally, this study underscores the importance of laws and institutional design in promoting political equality in the United States.